Nanobeads formation for anticancer drug release controlled by electrospinning - Muhammad Syafiq, Abd Rahman (2013)
Anticancer drug nowadays have become one of the most important industry in the world. In order to improve drug delivery, the used of nanoparticles is the main purpose for this research study. The objectives for this study are to investigate the morphology of nanoparticles produced based on different molecular weight of and concentration of Polyethylene Oxide (PEO). In this research, a very high molecular weight (MR) PEO is used as the core polymer. Two types of PEO used are with 400 000 MW and 900 000 MW. There are two types of solvents used that are distilled water and ethanol. Whey protein is used because it containing Cysteine, one of the sulphur-containing amino acid and has same properties as anticancer drug. Henceforth, whey protein is used because it is easily to purchase and cheaper. PEO acts as shell that encapsulated the drug. There are two main processes for the nanoparticles preparation that are solution preparation and electrospinning. Four types of solution are prepared; PEO with water, PEO with Ethanol, PEO with protein, and PEO with protein and ethanol. All samples are prepared till 10 mL and 20 mL and then go through the electrospinning about 5 hours. After electrospinnig the samples will be analyzed under Field Emission Scanning Electron Microscopy (FESEM) to observe the morphology of nanoparticles and Energy Dispersive X- Ray (EDX) for sulphur determination. The resulted obtained showed the lower the viscosity, the more the formation of nanobeads. Lower molecular weight also affects the nanobeads formation as lower molecular weight is more beads than higher molecular weight.